Fungal infection after keratoplasty and the role of antifungal supplementation to storage solution: a review. Issue 8 (3rd December 2019) - Thareja, Tarika; Kowalski, Regis; Kamyar, Roheena; Dhaliwal, Deepinder; Jeng, Bennie H; Tu, Elmer; Jhanji, Vishal
Abstract : Fungal infection after corneal transplantation is a rare, yet potentially devastating, postoperative complication and has become a growing concern for the transplant surgeon and eye banking community. The Eye Bank Association of America (EBAA) has reported an increasing trend in the rate of postkeratoplasty fungal infections and a reversal in the previously documented predominance of bacterial over fungal infections. Additionally, several studies have confirmed a high correlation between positive corneoscleral donor rim fungal cultures and postoperative infections. Optisol GS (Bausch & Lomb, Irvine, California, USA), the most extensively used corneal storage solution in US eye banks, does not currently contain any antifungal supplementation. Although large randomised control trials evaluating the efficacy and safety of routine antifungal supplementation to corneal storage solution are lacking, several investigative studies have assessed the role of antifungal agents in reducing fungal contamination of donor corneas without causing undue corneal toxicity. This review will present the current epidemiology of postkeratoplasty fungal infections and evidence for obtaining routine fungal rim cultures and antifungal supplementation of storage solution.